2000
DOI: 10.1038/labinvest.3780123
|View full text |Cite
|
Sign up to set email alerts
|

Response of Nasopharyngeal Carcinoma Cells to Epstein-Barr Virus Infection In Vitro

Abstract: SUMMARY:Many nasopharyngeal carcinoma (NPC) biopsy specimens contain Epstein-Barr virus (EBV). However, the response of NPC cells to EBV infection in vitro and in vivo is not well characterized. In this experiment we infected NPC cells with EBV particles through endocytosis of a complex of EBV immunoglobulin A (IgA) secretory component (SC) protein to observe the response of host cells to the foreign viral infection in vitro. We found that EBV particles were endocytosed and stabilized in NPC nuclei 24 hours af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 31 publications
(25 reference statements)
4
35
0
Order By: Relevance
“…The expression of SOCS-1 and IL-6 was examined by PCR using specific primer as listed in Table 1. For amplification of IL-6, a touch-down PCR cycle as described by Lin et al (2000a) was used. As an internal control, amplification of b-actin was performed.…”
Section: Rna Isolation and Reverse Transcription -Pcr (Rt -Pcr) For Smentioning
confidence: 99%
“…The expression of SOCS-1 and IL-6 was examined by PCR using specific primer as listed in Table 1. For amplification of IL-6, a touch-down PCR cycle as described by Lin et al (2000a) was used. As an internal control, amplification of b-actin was performed.…”
Section: Rna Isolation and Reverse Transcription -Pcr (Rt -Pcr) For Smentioning
confidence: 99%
“…While infected epithelial cells may undergo clonal expansion and immortalization to develop NPC, B-lymphocytes with latent infection are predisposed to transformation with propensity to develop lymphomas (such as Burkitt's lymphoma, post-transplant B-cell lymphoma and Hodgkin's disease) [6,9]. Little is known of the mechanisms underpinning the different processes of EBV infection and why the EBV-infected NPC cells undergo increased proliferation [19]. Cytogenetic studies have shown that there are many chromosomal abnormalities in NPC tissues suggesting that genomic instability is a common feature in NPC development [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…10 The primer sequences for the mdm2 probe were adapted from a paper by Sigalas et al 19 They were L (sense) GCA GGG GAG AGT GAT ACA GAT and R (antisense) GAT GGC TGA GAA TAG TCT TCA containing 348 bp in between two primers. For internal control, the actin primer sequences were used as published previously.…”
Section: Rna Expression In Ebv à and Ebv þ Npc Cells And Biopsy Specimentioning
confidence: 99%
“…6,7 Research findings on these cell lines and their original biopsy specimens indicate that EBV plays a major role in promoting tumor progression in NPC pathogenesis. [8][9][10][11][12] In one of our experiments, 12 we used severe combined immunodeficiency (SCID) mice to produce EBV þ and EBV À xenografts, in which certain oncogenes such as EGFR were only expressed in a fraction of EBV À tumor cells; EBV infection could enhance those cells to express the EGFR gene, but could not turn on the EGFR gene in other tumor cells which did not express this gene. 12 However, this finding was a morphological observation.…”
mentioning
confidence: 99%